(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
This article explores the significance of speaking skills in enhancing communication compensation strategies among university students. Speaking is a crucial component of language acquisition, allowing learners to overcome linguistic barriers, reduce misunderstandings, and express ideas clearly. The paper analyzes the role of speaking in academic and social communication, effective classroom methodologies, and international experiences. It also presents scientific findings showing that well-developed speaking skills directly impact students’ academic performance and confidence in interpersonal communication.